INNOVATIVE LEADERSHIP FACTORS AFFECTING ADMINISTRATION EFFECTIVENESS OF HIGHER ART COLLEGES IN HEILONGJIANG PROVINCE - Yingting, Zhao; Muangman, Pornthep; Tipanark, Peerapong (วารสารวิจัยธรรมศึกษา, 2025)
The objectives of this research were: (1) To study the factors of Innovative Leadership Administrators and the components of administration effectiveness. (2) To explore factors of Innovative Leadership Administrators affecting Administration effectiveness of higher art Colleges in Heilongjiang Province and (3) To propose the guideline for improving the Administrators’ leadership of higher art Colleges in Heilongjiang Province. The research was a mixed method between quantitative research and qualitative research. Population consisted of 1,889 administrators, teachers and staff from 17 public higher art colleges in Heilongjiang Province, the People's Republic of China. obtained by stratified sampling method, totaling 330 samples. The key informants were 9 administrators from 17 public higher art colleges, obtained through a purposive sampling method. The expert for Focus Group Discussion were comprised of seven experts to confirm model. The instruments used for data collection included a five-point rating scale questionnaire and validation checklist. The statistics used for data analysis were frequency, percentage three managerial guidelines for component of Innovative thinkingmean, Standard Deviation（EFA）, and Confirmatory Factor Analysis. Both in depth interviews and Focus Group Discussion were analyzed by content analysis. The research findings revealed that; (1) There were six factors of Innovative Leadership Administrators, as follows: Innovative thinking, Innovation ability, Leadership style, Innovation management, Organizational innovation, Innovation environment, and six components of administration effectiveness, and Institutional system, Performance appraisal, Teaching staff, Talent training, Education innovation, social value. (2) The six have an impact factor of Innovative Leadership Administrators affecting Administration effectiveness of higher art Colleges in Heilongjiang Province. as follows: Innovative thinking, Innovation ability, Leadership style, Innovation management, Organizational innovation, Innovation environment, (3) The developed implementation guideline contained 21 items used for improving the Administrators’ leadership of higher art Colleges in Heilongjiang Province.